Genetic base-broadening of cacao for precocity and cropping efficiency. Issue 6 (8th August 2016) - Padi, Francis Kwame; Ofori, Atta; Akpertey, Abraham
Abstract: Introduction of clones from genetic groups that are underrepresented in the pedigree of commercial cacao varieties in West Africa represents an important aspect of cacao improvement strategy of broadening the genetic base to overcome current yield stagnation of the crop. The objective of the present study was to determine the combining abilities of more recently introduced cacao clones for yield and cropping efficiency in the early bearing years. Seven recently introduced clones were crossed as males to five clones commonly used in the seed gardens in Ghana using a North Carolina II design. The 35 F1 varieties and one commercial variety were evaluated in the field from June 2010 to March 2015 for four traits: increase in trunk cross-sectional area in the juvenile, and in the pod-bearing phases, bean yield and cropping efficiency. Though both GCA and SCA variances were significant for all traits, the ratios of GCA:SCA were much smaller than unity, indicating the importance of non-additive effects in the control of the traits. Among the set of clones therefore, prediction of F1 variety performance cannot be based on the GCA or per se (average) performance of the clones. Six varieties were more precocious, and eight had higher cropping efficiencies than the standard variety. Bean yields ranged from 0.74 to 1.05 t/ha/year in the fourth and fifth years after planting among the top six varieties. The study provides evidence of the large potential for productivity increase through the use of cacao clones beyond Pound's early introductions into West Africa.